Aspects of vibration in bridge-girders - Weinheimer, Stefanie (Department of Civil Engineering, 2016)
A theoretical comparative study of methods for determining natural frequencies of vibration and their corresponding mode shapes is presented for the case of cantilevers, simply supported and continuous beam structures. Different methods are used, such as classical, energy and matrix methods. Effects of mass lumpings are investigated. A literature review is given for the general problem of dynamic behaviour of highway bridges, including the passage of heavy vehicles.